68Ga-Radiolabeling and Pharmacological Characterization of a Kit-Based Formulation of the Gastrin-Releasing Peptide Receptor (GRP-R) Antagonist RM2 for Convenient Preparation of [68Ga]Ga-RM2 - Adrien Chastel; Delphine Vimont; Stephane Claverol; Marion Zerna; Sacha Bodin; Mathias Berndt; Stéphane Chaignepain; Elif Hindié; Clément Morgat (MDPI AG, 2021)
Background: [68Ga]Ga-RM2 is a potent Gastrin-Releasing Peptide-receptor (GRP-R) antagonist for imaging prostate cancer and breast cancer, currently under clinical evaluation in several specialized centers around the world. Targeted radionuclide therapy of GRP-R-expressing tumors is also being investigated. We here report the characteristics of a kit-based formulation of RM2 that should ease the development of GRP-R imaging and make it available to more institutions and patients. Methods: Stability of the investigated kits over one year was determined using LC/MS/MS and UV-HPLC. Direct 68Ga-radiolabeling was optimized with respect to buffer (pH), temperature, reaction time and shaking time. Conventionally prepared [68Ga]Ga-RM2 using an automated synthesizer was used as a comparator. Finally, the [68Ga]Ga-RM2 product was assessed with regards to hydrophilicity, affinity, internalization, membrane bound fraction, calcium mobilization assay and efflux, which is a valuable addition to the in vivo literature. Results: The kit-based formulation, kept between 2 °C and 8 °C, was stable for over one year. Using acetate buffer pH 3.0 in 2.5-5.1 mL total volume, heating at 100 °C during 10 min and cooling down for 5 min, the [68Ga]Ga-RM2 produced by kit complies with the requirements of the European Pharmacopoeia. Compared with the module production route, the [68Ga]Ga-RM2 produced by kit was faster, displayed higher yields, higher volumetric activity and was devoid of ethanol. In in vitro evaluations, the [68Ga]Ga-RM2 displayed sub-nanomolar affinity (Kd = 0.25 ± 0.19 nM), receptor specific and time dependent membrane-bound fraction of 42.0 ± 5.1% at 60 min and GRP-R mediated internalization of 24.4 ± 4.3% at 30 min. The [natGa]Ga-RM2 was ineffective in stimulating intracellular calcium mobilization. Finally, the efflux of the internalized activity was 64.3 ± 6.5% at 5 min. Conclusion: The kit-based formulation of RM2 is suitable to disseminate GRP-R imaging and therapy to distant hospitals without complex radiochemistry equipment.